Water quality mitigation strategy analysis of the Salton Sea, California, using the Delft-3D modeling suite - Lee, Meng-Chen; Stenstrom, Michael K. (Frontiers in Sustainable Resource Management, 2023)
The Salton Sea is the largest lake in California and is a shallow, hypersaline lake. The endorheic lake has been maintained by agricultural return flows from Imperial Valley farming and two rivers- the New River and Alamo River- which originate in Mexicali, Mexico. The current salinity is at 74 ppt and is expected to increase due to the Quantification Settlement Agreement signed in 2003, stipulating the transfer of nearly 0.616 km3 per year of Colorado River water to urban areas for up to 75 years. This has resulted in inflows reduction, and the dust storms created by the dried-up playa have become a prominent risk to public health in the region. Massive fish and bird kills began in the 1980s and continued to occur periodically. In this study, the Delft3D numerical modeling suite- FLOW, WAVE, and WAQ- was utilized to investigate the transport and cycling of nutrients under the influence of wind-induced sediment resuspension activity. The three-dimensional hydrodynamic and water quality combined model was applied to simulate mitigation scenarios to assess long-term effects on salinity and water quality of 1) emerged islands as a natural-based solution, 2) seawater import/export, and 3) seawater import/export in addition to treating tributary rivers to remove nutrients. Overall, this study supported the findings from previous studies and showed that sediment resuspension is the driving force for nutrients cycling in the water column and that emerged islands have long-term potential to enhance burial activity for pollutants removal in the Salton Sea. Furthermore, the seawater import/export scenario showed promising results of reducing salinity level from 46 ppt to 38-39 ppt in two years. The 3D hydrodynamic/water quality model developed in this work is the latest 3D ecological model tailored to the Salton Sea’s system and has the capacity to improve understanding of the complicated water quality dynamics changes in various restoration concepts. This study demonstrated that being able to explore the full potentials of restoration designs using a comprehensive 3D water quality modeling is critical in achieving wholesome planning that will create environmental, social and economic benefits in the long term for the Salton Sea.